3-D thermal structure and dehydration near the Chile Triple Junction and its relation to slab window, tectonic tremors, and volcanoes ... - Iwamoto, Kaya; Suenaga, Nobuaki; Yoshioka, Shoichi; Ortega-Culaciati, Francisco; Miller, Matthew; Ruiz, Javier (figshare, 2024)
Abstract The southern Chile subduction zone is a complex tectonic environment, where the Chile Ridge, the Nazca (NZ) and Antarctic (AN) plates subduct underneath the South American (SA) plate. The intersection between the NZ, AN and SA plates is referred to as the Chile Triple Junction (CTJ). In this region, a gap, often referred to as a slab window, has been formed between the NZ and AN slabs due to the divergence in their plate motion velocities, with volcanoes existing mainly above the subducted NZ and AN plates. In this study, we constructed a three-dimensional thermomechanical model associated with simultaneous subduction of the NZ and AN plates near the CTJ. The results show that the current temperature distributions on the upper surface of the slabs are higher closer to the Chile Ridge, and the AN plate has a distribution of elevated temperatures relative to the NZ plate at the same depth due to the northward migration of the CTJ and the slower convergence rate of the AN plate. Moreover, we calculated ...